Enhanced Efficiency and Stability of Carbon‐Based Perovskite Solar Cells by Eva Interface Engineering. Issue 10 (6th February 2022) - Wang, Haobin; Qiang, Yue; Zheng, Shenshen; Wei, Peng; Xie, Yahong
Abstract: Nanocrystalline tin (IV) oxide (SnO2 ) as an electron‐transport layer (ETL) has unique advantages in realizing highly efficient and stable planar perovskite solar cells (PSCs), especially showing great potential in the low‐temperature preparation of large‐area flexible carbon‐based PSCs (C‐PSCs). However, the high trap density on the surface of SnO2 tends to cause serious nonradiative recombination losses, thereby reducing photoelectric performance. In this work, an inexpensive and easily obtained polymer poly(ethylene‐co‐vinyl acetate) (Eva) is used as a interfacial modifier to reduce the interfacial defects and nonradiative recombination losses at the SnO2 /perovskite interface. As a result, the crystallinity and conductivity of the perovskite layer are significantly increased, and the charge lifetime and stability are effectively improved. The Eva modified SnO2 ‐based C‐PSCs obtain an optimal power conversion efficiency (PCE) of 12.29%, which is 25.7% higher than that of 9.78% for the unmodified C‐PSCs. Furthermore, the unencapsulated devices maintain 88.6% and 91.9% of the initial PCE over 1 month in ambient air for the unmodified and Eva‐modified C‐PSCs, respectively. The study provides valuable experience for the development of highly efficient and stable C‐PSCs using common polymers for interface modification engineering. Abstract : The high trap density on the surface of SnO2 ETL tends to cause serious nonradiative recombination losses, thereby reducing photoelectric performance. C‐PSCs with PCE of 12.29% are obtained by Eva interface engineering. The unencapsulated device maintains 91.9% of the initial PCE over 1 month in ambient air for the Eva‐modified C‐PSCs.